The Year 2024, Nigeria’s Physiology Family and the Plethora of Exits (Nigerian Journal of Physiological Sciences, 2024)
The Physiological Society of Nigeria mourns the loss, in the first half of the year 2024, of five distinguished members who left indelible marks and footprints in the sand of time. The contributions of Professors Chikodi Anigbogu (23 December 1953 – 2 January 2024); David Oyebola (1 October 1945–13 February 2024); Anthony Ebeigbe (22 August 1950 – 30 May 2024); Vincent Iyawe (14 April 1953 – 8 June 2024) and Olusoga Solofa (24 January 1947 – 10 June 2024) to the establishment and growth of the Physiological Society of Nigeria are well appreciated